Divisibility Of Integer By Matrix Multiplication Method - Ahmed1, Ali. A. M.; Salman, M. A.; Al-Qadasi, Miason; Pawar, D. D.; Bondar, K. L. (Journal of Amran University, 2022)
In this paper we present a new divisibility method by using matrix multiplication to test any number X is divisible or not divisible by any integer. If X is not divisible, then this method is also useful nding the remainder. Keywords: Integer division, divisibility rules, matrix multiplication method AMS Classi cation: 11A05, 11A51 JEL Classi cation: C60, C65